Kontribusi Psikologi Pendidikan bagi Pendidik/Kepala Sekolah, Guru Pendidikan Agama Kristen (PAK) dalam Pembelajaran, Guru Sekolah Minggu, Pendeta, Penatua, Pelayan Gereja - Armela Nababan; Nursalina Sihombing; Marthalena Lumbangaol; Enjelina Enjelina; Wilson Simajuntak (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to examine the contribution of educational psychology in the context of Christian education, particularly for educators, school principals, Christian Religious Education (CRE) teachers, Sunday school teachers, pastors, elders, and church servants. This theoretical study shows that educational psychology helps in understanding the characteristics of learners, optimizing teaching methods, building effective teacher-student relationships, and enhancing motivation and involvement in the learning and preaching process. The research method used is a descriptive qualitative approach, collecting data through a review of books, literature, journals, notes, and relevant reports. Educational psychology plays a significant role for all those involved in Christian education and ministry. CRE teachers and Sunday school teachers have a crucial role in instilling faith values in the younger generation by understanding the learning needs of children according to their cognitive and spiritual development stages. This enables them to deliver God's word in an engaging and meaningful way. Meanwhile, pastors, elders, and church servants require an understanding of educational psychology to carry out more wise pastoral ministry. Psychological understanding helps them provide spiritual guidance, counseling, and support for members who are struggling. Educational psychology also equips church servants to lead with empathy, listen with their hearts, and guide the congregation towards true spiritual restoration. The integration of educational psychology with Christian faith significantly impacts the improvement of learning and church ministry, producing individuals who are intellectually, emotionally, and spiritually balanced.